Value transmission in primary schools: are teachers’ acculturation orientations a moderator? - Auer, Petra; Makarova, Elena; Döring, Anna K.; Demo, Heidrun (Frontiers in Education, 2023)
The transmission of human values to primary school pupils is key, which is acknowledged in curricula in a variety of cultural contexts worldwide. The present study presents data from the multicultural and multilingual region of Bolzano in Northern Italy (n=422 pupils in k=30 classrooms). In addition to class teachers’ values as predictors of their pupils’ values we investigated whether teachers’ acculturation orientations would strengthen the relationship between teachers’ and children’s values, thereby acting as moderators. We focused on the opposing acculturation orientations of integration versus exclusion. A multilevel analysis showed that teachers’ conservation values (tradition, conformity, and security) significantly predicted their pupils’ conservation values, and that teachers’ openness to change values (self-direction, stimulation, and hedonism) significantly predicted their pupils’ openness to change values. This indicates successful value transmission in the classroom. Teachers’ self-transcendence (Benevolence and universalism) and self-enhancement (achievement and power) values did not significantly predict pupils’ values. As expected, teachers’ acculturation orientations were related to their values, but they did not play a role in predicting pupils’ values. Implications for value transmission in the classroom are discussed.